1987
DOI: 10.1128/jvi.61.3.845-850.1987
|View full text |Cite|
|
Sign up to set email alerts
|

Resolution of a polyomavirus-mouse hybrid replicon: viral function required for recombination

Abstract: RmI, a circular chimera made of the polyomavirus (Py) genome with an insertion of mouse DNA (Ins), effectively undergoes intramolecular recombination in normal mouse cells, as indicated by the conversion of cloned RmI (RmIL) into unit-length Py DNA in transfected cultures. To follow the fate of the cellular component of RmI after recombination, the origin of simian virus 40 (SV40) DNA was inserted into the Ins region of RmIc, generating a new molecular species designated SV-RmIc. Intramolecular recombination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Alternatively, pl-1 could be more likely to recombine than RmI precisely because it is less able to replicate. Such would be the case if recombination depended on a limiting factor also needed for replication (18). In either case, the data clearly established that maximal accumulation of P155 was compatible with minimal accumulation of its precursor, a finding that proved to be important for understanding the recombination event under study (18).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Alternatively, pl-1 could be more likely to recombine than RmI precisely because it is less able to replicate. Such would be the case if recombination depended on a limiting factor also needed for replication (18). In either case, the data clearly established that maximal accumulation of P155 was compatible with minimal accumulation of its precursor, a finding that proved to be important for understanding the recombination event under study (18).…”
Section: Resultsmentioning
confidence: 82%
“…Note that material migrating faster than pI-1 itself was not detectable in the stock of plasmid DNA used as a marker: this is not surprising because, if it were generated by homologous recombination from pl-1, P155 could not replicate in E. coli. Annealing of a similar blot with a cellular DNA probe specific for Ins (18) indicated that if formed, IR, the reciprocal of P155 (see Fig. 3), does not accumulate detectably after transfection with Rmlc (not shown).…”
Section: Resultsmentioning
confidence: 98%
“…From this observation and from thos 2-1.54 and 3-1.82, it is tempting to conclude over occurs preferentially downstream from the tered S repeat moving in either direction from tl position effect suggests that recombination d process initiated at the ORI, such as replication tion. Actually, we have already shown thal sequences with a cis-inhibitory effect on r transcription into RmI prevents recombinatio repeats (28). A protein which would travel along the DNA while carrying out either process, such as large T antigen * P155 during replication (28), could also be required for recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Here it is known that T antigen acts at some point prior to or during the homologous recombination process that yields excised circular viral DNA. Several other investigations of SV40 and polyomavirus infected or transformed cells also suggest that T antigen functions in DNA recombination (Michel et al, 1967;Nichols et al, 1978;Brown and Basilico, 1982;Jasin et al, 1985;Norkin et al, 1985;Rubnitz and Subramani, 1985; Piche and Bourgaux, 1987;Heinzel et al, 1988; Gurney and Gurney, 1989;Strauss et al, 1989) most probably in conjunction with its DNA replication function (Stary et al, 1989). In addition to these possible in vivo roles in some recombination processes, T antigen shows amino acid sequence similarity to the Escherichia coli RecA protein, the key enzyme of recombination in the bacterial cell (for review see Cox and Lehman, 1987;West, 1988;Smith, 1989), and antibodies raised against T antigen cross-react with RecA (Seif, 1982).…”
Section: Introductionmentioning
confidence: 92%